2011
DOI: 10.4196/kjpp.2011.15.5.307
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Non-cholinergic Intrapancreatic Nerves, Serotonergic Nerves, on Pancreatic Exocrine Secretion in the Isolated Perfused Rat Pancreas

Abstract: It has been rereported that axons which display 5-hydroxytryptamine (5-HT) immunoreactivity are abundant in the pancreas and the majority of serotonergic axons terminate within intrapancreatic ganglia, islet and acini. This histological result strongly suggests that intrapancreatic serotonergic nerves could affect to the pancreatic endocrine and exocrine secretion. Thus, this study was aimed to investigate whether intrapancreatic serotonergic nerves could affect pancreatic exocrine secretion and an action mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…For example, the cholinergic nerves [6] and the sympathoadrenal axis [7] can modulate insulin secretion from pancreatic β-cells, demonstrating that the nervous system can regulate insulin secretion directly, and in addition to indirect effects on metabolism through the regulation of food intake, body temperature, sleep and activity [8]. There is evidence that the pancreas receives serotonergic nervous inputs from vagus and enteric nervous system [9]. The serotonin (5-hydroxytryptamine; 5-HT) secreted form these intrapancreatic nerves may act as a stimulator or inhibitor of pancreatic exocrine secretion, depending on the expression of different receptor subtypes [9], but whether the 5-HT system could play a role in pancreatic endocrine function is largely unknown [10], [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the cholinergic nerves [6] and the sympathoadrenal axis [7] can modulate insulin secretion from pancreatic β-cells, demonstrating that the nervous system can regulate insulin secretion directly, and in addition to indirect effects on metabolism through the regulation of food intake, body temperature, sleep and activity [8]. There is evidence that the pancreas receives serotonergic nervous inputs from vagus and enteric nervous system [9]. The serotonin (5-hydroxytryptamine; 5-HT) secreted form these intrapancreatic nerves may act as a stimulator or inhibitor of pancreatic exocrine secretion, depending on the expression of different receptor subtypes [9], but whether the 5-HT system could play a role in pancreatic endocrine function is largely unknown [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the pancreas receives serotonergic nervous inputs from vagus and enteric nervous system [9]. The serotonin (5-hydroxytryptamine; 5-HT) secreted form these intrapancreatic nerves may act as a stimulator or inhibitor of pancreatic exocrine secretion, depending on the expression of different receptor subtypes [9], but whether the 5-HT system could play a role in pancreatic endocrine function is largely unknown [10], [11]. Furthermore, it has been suggested that pancreatic β-cells can secrete 5-HT by themselves, which could represent a form of autocrine regulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…α-Amylase activity in the pancreatic juice was determined by the method of Rick and Stegbauer (1974) [16]. In brief, 1 mL starch solution (1%, w/v) is put in 1 mL phosphate buffer (10 mM KH 2 PO 4 , 10 mM Na 2 HPO 4 , 10 mM NaCl, pH 6.9) and mixed with 1000-3000 times diluted pancreatic juice (20 µL).…”
Section: Methodsmentioning
confidence: 99%